2006
DOI: 10.4314/ajtcam.v3i2.31161
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of some Cameroonian medicinal plants against common pathogenic bacteria

Abstract: We screened forty crude extracts of twenty Cameroonian medicinal plants commonly used to treat bacterial infections for broad spectrum antibacterial activity, as a more affordable alternative against resistant organisms. The extracts were screened on common pathogenic gram negative and gram positive bacteria initially by the disc diffusion method followed by the tube dilution method. Using discs containing 30µg of extract, Escherichia coli showed sensitivity to 23 extracts with diameter of zone of inhibition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…However, extracts of Emilia coccinea, Eryngium foetidium, Aulatandra kamerunensis, Tapeinachilus ananassae, Euphorbia hirta, Acanthus montanus and Scleria verrucosa were weakly active against the isolates. Although our results showed lower activities of these extracts relative to previous findings (Nkuo-Akenji et Akinyemi et al, 2005;Ngemenya et al, 2006), which reported potent activity of most of the extract of these plants against other gram-negative and -positive bacteria, they however corroborate their reports. This variation may be due to the dose of extracts used in the different studies, the solvent used for extraction, the method of bioassay employed, the age of the plant, and the plant parts used.…”
Section: Resultscontrasting
confidence: 46%
See 2 more Smart Citations
“…However, extracts of Emilia coccinea, Eryngium foetidium, Aulatandra kamerunensis, Tapeinachilus ananassae, Euphorbia hirta, Acanthus montanus and Scleria verrucosa were weakly active against the isolates. Although our results showed lower activities of these extracts relative to previous findings (Nkuo-Akenji et Akinyemi et al, 2005;Ngemenya et al, 2006), which reported potent activity of most of the extract of these plants against other gram-negative and -positive bacteria, they however corroborate their reports. This variation may be due to the dose of extracts used in the different studies, the solvent used for extraction, the method of bioassay employed, the age of the plant, and the plant parts used.…”
Section: Resultscontrasting
confidence: 46%
“…To determine the MBC, 0.2 mL of the contents of the MIC tubes were serially diluted 10-fold in 0.9% physiological saline (Ngemenya et al, 2006). A loop full was taken from each tube and inoculated onto BHI agar plates.…”
Section: Determination Of Minimum Bactericidal Concentration (Mbc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the weak activity demonstrated by these extracts in vitro to the organism, does not necessarily imply that they would demonstrate weak activities in vivo. As with some drugs, some of these plant maybe more potent in vivo due to metabolic transformation of their components into highly active intermediates (Ngemenya et al, 2006). Such results provide evidence that these plants might be potential sources of new antibacterial agents even against some resistant strains.…”
Section: Resultsmentioning
confidence: 95%
“…Weak activities observed in vitro however should not be interpreted to mean that the extracts would give similar activity in vivo. Some of these plant extracts, as with some drugs, may be more potent in vivo due to metabolic transformation of their components into highly active intermediates or their interaction with the immune system (Garcia et al, 2003;Ngemenya et al, 2006). Table 3 shows the anti-inflammatory activity of the various extracts in both COX-1 and COX-2 assays.…”
Section: Resultsmentioning
confidence: 98%